Metabolic regulation of inflammasomes in inflammation. Issue 2 (8th April 2019) - Yang, Qiuli; Liu, Ruichen; Yu, Qing; Bi, Yujing; Liu, Guangwei
Summary : Inflammasome activation and subsequent inflammatory cytokine secretion are essential for innate immune defence against multiple stimuli and are regarded as a link to adaptive immune responses. Dysfunction of inflammasome activation has been discovered at the onset or progression of infectious diseases, autoimmune diseases and cancer, all of which are also associated with metabolic factors. Furthermore, many studies concerning the metabolic regulation of inflammasome activation have emerged in recent years, especially regarding the activity of the NLRP3 inflammasome under metabolic reprogramming. In this review, we discuss the molecular mechanisms of the interactions between metabolic pathways and inflammasome activation, which exerts further important effects on various diseases. Abstract : We discuss the molecular mechanisms of the interactions between metabolic pathways and inflammasome activation, which exert further important effects on various diseases.